MENINGKATKAN MINAT BELAJAR PRAKARYA MELALUI MODEL PEMBELAJARAN KONSTRUKTIVISME UNTUK SISWA KELAS VII SMPN 1 KARANGPLOSO - Sri Sulastri (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2017)
This study aims to increase interest and student learning outcomes in learning the craft subject using constructivism approach. This study used classroom action research design in three cycles. The study assigned 32 students of the seventh grade of SMPN 1 Karangploso, Malang. The study revealed that (1) constructivist approach could enhance the students' learning activities showing an increase in cycle 1 to cycle 3 respectively 58.82%, 73.53% and 88.24%; (2) students ’ learning outcomes improved from 47.06% in cycle 1, 52.94% in cycle 2, and 78.13% in cycle 3. This means the achievement of learning the craft subject using a constructivist approach was quite good attaining Y 75%.